Penetrating Ocular Injury in a Young Child: A Case Report Highlighting the Urgency of Corneoscleral Repair - Raule, Agnestya Christine Zely; Mayangsari, Dian (Bali Medical and Wellness Journal, 2025)
Introduction: Penetrating ocular trauma is an ophthalmologic emergency that can lead to significant vision loss, especially in children. This report describes the presentation and management of a severe case in a young child from a remote area. Case Description: A 3-year-old girl presented with a left eye injury after being struck by a nail. Examination revealed a superior eyelid laceration, a full-thickness corneal laceration with iris prolapses, and hyphema. Initial visual acuity in the affected eye was 1/300. The patient underwent immediate corneoscleral repair followed by postoperative treatment with systemic and topical antibiotics, corticosteroids, and tetanus prophylaxis. Discussion: Prompt surgical intervention is essential in cases of penetrating ocular trauma to preserve globe integrity and minimize the risk of complications such as endophthalmitis and amblyopia. Despite immediate surgical intervention, the patient's visual acuity remained poor two days post-surgery Conclusion: This case underscores the critical need for early recognition, timely surgical intervention, and diligent follow-up care in the management of pediatric penetrating ocular trauma, particularly in remote areas where access to specialized care may be limited.